Peripapillary border tissue of the choroid and peripapillary scleral flange in human eyes - Jonas, Rahul A.; Holbach, Leonard (Acta Ophthalmologica, 2019)
Purpose: To assess dimensions and associations of the peripapillary border tissue of the choroid (PBT-C) and peripapillary scleral flange (PBT-S). Methods: The histomorphometric investigation included histological sections of enucleated eyes of Caucasian patients. Using light microscopy, the PBT dimensions were measured. Results: The study included 85 eyes (85 patients) with an age of 62.0 years (14.1 years) (mean (SD)) (range:37–87 years) and mean axial length of 26.7 mm (3.5 mm) (range:21.0–37.0 mm). Thicker PBT-C thickness (mean: 68.8 μm (35.7 μm)) was associated with shorter axial length (p < 0.001; standardized regression coefficient beta: −0.50), and longer PBT-C length (mean: 531 μm (802 μm)) was correlated with longer axial length (p < 0.001;beta:0.66). PBT-C cross-sectional area (mean 17 050 μm2 (10 420 μm2)) was not significantly associated with axial length (p = 0.37). Decreasing with longer axial length (p < 0.001;beta:0.64), the angle between PBT-C and Bruch's membrane was approximately 90° in non-highly myopic eyes without overhanging Bruch's membrane (BM), it ranged between 100° and 180° in eyes with BM overhanging into the intrapapillary region, and it was close to 0° in eyes with parapapillary gamma zone. Thicker thickness of PBT-S (mean:83 μm (21 μm)) was correlated with presence of glaucoma (p = 0.02). Optic nerve pia mater thickness (mean:109 μm (44 μm)) increased with glaucoma presence (p = 0.046;beta:0.31) but not with axial length (p = 0.34). Conclusions: Peripapillary border tissue of the choroid (PBT-C) and PBT-S as continuation of the optic nerve pia mater are distinct structures, with PBT-C remodelling during myopic axial elongation and PBT-S being mostly independent of axial elongation. PBT-C and PBT-S may be of importance for the optic nerve head biomechanics and PBT-C for separation of the choroidal space from the intrapapillary compartment.
CRIS-Team Scopus Importer:2019-08-27
Keywords: axial length; Bruch's membrane; choroid; histomorphometry; lamina cribrosa; myopia; parapapillary beta zone; parapapillary gamma zone; peripapillary border tissue; peripapillary scleral flange